Epidemiology and survival of hepatocellular carcinoma in Turkey: Outcome of multicenter study - Alacacioglu, Ahmet; Somali, Isil; Simsek, Ilkay; Astarcioglu, Ibrahim; Ozkan, Metin; Camci, Cemalettin; Yilmaz, Ugur (Oxford Univ Press, 2008)
Objective: Hepatocellular cancer (HCC) is one of the important health problems in Turkey. We aimed to determine the clinical and demographic features of HCC in the Turkish population and to evaluate the prognostic and survival features. Method: Two hundred and twenty-one patients with HCC from five hospitals in Turkey are included in this study. Results: In 44.4% of the 221 patients with hepatitis B virus and in 21.3% of the 221 patients with hepatitis C virus were found to be responsible for HCC etiology. It has been shown that HCC developed on cirrhosis basis in 74.2% of the patients. HCC was presented with single solitary nodule in 69.2% of the patients. Non-liver metastasis was present in 12.5% of the patients. In 21.7% of the patients, alpha-fetoprotein (AFP) levels were above the diagnostics level of 400 ng/ml. The median overall survival (OS) of 221 patients was 14 months. The median OS of the patients with Child-Pugh A class was significantly longer than that with Child-Pugh B and C classes. The OS of the individuals with normal AFP levels was also longer than that with high AFP levels. The OS of the patients with Stage I HCC according to tumor node metastasis (TNM) classification, the female patients and the treated patients group was found to be significantly good. Conclusion: In conclusion, the viral etiology (hepatitis B and C infections) in Turkish population is found to be an important factor in HCC development. The Child-Pugh classification, AFP levels, TNM classification, being female and treatment were determined to be important prognostic factors in HCC patients.
Keywords: hepatocellular cancer; HCC; prognosis; Turkey